Inventing Latin America Under the Good Neighborhood Policy: The Case of the MoMA Collection, 1943 - Matallana, Andrea (International Journal of Culture and Art Studies, 2022)
This article describes the strategies of the North American government to help establish a Latin American Collection in the Museum of Modern Art (MoMA) and the role that Lincoln Kirstein had as a collector of the works that made up the collection. The dialogue that Kirstein had with various personalities of the culture in the tasks of exhibition and collection is analyzed. We emphasize how the fine arts were spaces of political weighting, and areas usable by Good Neighbor politics. Finally, it is explained what kind of Latin American art was collected to make up the collection in 1943, and what idea of Latin America was represented through that selection. Â The research uses primary sources collected from MoMA Archives, Rockefeller Personal Archives, New York Public Library and Lincoln Kirstein Archives. The comparative method in history was used to review the different cases analyzed.